(q-4)*3=24

Simple and best practice solution for (q-4)*3=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (q-4)*3=24 equation:


Simplifying
(q + -4) * 3 = 24

Reorder the terms:
(-4 + q) * 3 = 24

Reorder the terms for easier multiplication:
3(-4 + q) = 24
(-4 * 3 + q * 3) = 24
(-12 + 3q) = 24

Solving
-12 + 3q = 24

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 3q = 24 + 12

Combine like terms: -12 + 12 = 0
0 + 3q = 24 + 12
3q = 24 + 12

Combine like terms: 24 + 12 = 36
3q = 36

Divide each side by '3'.
q = 12

Simplifying
q = 12

See similar equations:

| x^2+2x+123=0 | | -12n+8=-10n-18 | | 2z/9-1=2 | | (5n^6+16n^4+20)-(7n^4+3n^6-7)= | | -3z=34 | | X/10-1=-8 | | -4y^2-y+2=0 | | z-3y=-1 | | Z/7-9=9 | | 13x+4y=487 | | [-(y^4-y^2+1)-(y^4+7y^2+1)]+(6y^4-9y^2-12)= | | 3(2l+1)=81 | | 7x^3+26x^2-36x-8=0 | | -36x^4+289x^2-400=0 | | 5(a-8)=45 | | f(x)=9-6 | | 17y+6= | | X^3-3x^2-5x=-15 | | -2b-3b=2 | | 7/w-1/3 | | (u-8)*7=70 | | 2/3=6/× | | 6k^2-11k+3= | | 5(1p-1)=2p-5 | | .006=20log(x) | | 2x^4-8x+2=0 | | h+7h=42 | | 5(p-11)=2p-5 | | 5h+7=20 | | 2/7(4m-8)=12 | | -3(6s+6)= | | 2-3/5x=1/5x |

Equations solver categories